Efficacy of IVUS-Based Fractional Flow Reserve in Patients With Intermediate Left Main Stenosis - Khan, Muhammad Ismail; Shahzadi, Adeela; Muhammad, Dost; Nazeer, Nouman; Ahmed, Shahrukh (Biological and Clinical Sciences Research Journal, 2025)
Assessment of intermediate left main (LM) coronary artery stenosis remains clinically challenging. Wire-based fractional flow reserve (FFR) is considered the gold standard. Still, the use of intravascular ultrasound (IVUS)-derived functional indices, such as ultrasonographic flow ratio (UFR), is emerging as a potential non-wire alternative for physiological lesion assessment. Objective: To evaluate the diagnostic accuracy and efficacy of IVUS-based FFR (UFR) compared to wire-based FFR in patients with intermediate LM coronary artery stenosis. Methods: A prospective study was conducted at a tertiary care cardiology hospital from May 2024 to May 2025. A total of 100 adult patients with angiographically intermediate LM stenosis (defined as 50–70% diameter stenosis) were included. IVUS was performed using a motorized pullback device operating at 0.5 mm/s, from a distal point in the left coronary artery up to the aortic ostium. UFR was calculated based on IVUS pullback data. Wire-based FFR was recorded by positioning a pressure guidewire in the downstream coronary branches. The diagnostic performance of UFR was assessed using receiver operating characteristic (ROC) analysis, with wire-based FFR (cut-off <0.80) as the reference standard. Results: There was a moderate correlation between UFR and FFR (r = 0.692, p < 0.0001). UFR demonstrated a high area under the curve (AUC = 0.88; 95% CI: 0.91–0.99) for detecting functionally significant LM stenosis, outperforming angiography (AUC = 0.71, p < 0.001) and minimum lumen area (MLA) measurement (AUC = 0.79, p = 0.11). The optimal UFR threshold showed a diagnostic accuracy of 83.2%, superior to MLA ≤ 4.5 mm² (59.1%) and comparable to MLA ≤ 6.0 mm² (81.4%). Sensitivity for UFR, MLA ≤ 4.5 mm², and MLA ≤ 6.0 mm² was 92.7%, 48.6%, and 85.8%, respectively. FFR-based specificity was 57.6%, with a positive predictive value of 85.5%, negative predictive value of 78.3%, favorable likelihood ratio (+LR) of 2.19 (95% CI: 1.16–4.34), and negative likelihood ratio (–LR) of 0.09 (95% CI: 0.05–0.52). Conclusion: IVUS-derived FFR (UFR) demonstrated high diagnostic accuracy and sensitivity, comparable or superior to wire-based FFR in identifying functionally significant intermediate LM stenosis. UFR may offer a reliable, less invasive alternative to pressure-wire-based assessment in select patients.